Building the Foundations of Literacy: A Case Study on Oral Language, Alphabetic Knowledge, and Print Awareness in Early Childhood Education - Hanifah Tyas Mawarni; Avanti Vera Risti Pramudyani; Febritesna Nuraini; Dwi Hastuti (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
Literacy skills are the foundation for early childhood to face challenges in the 21st century, but based on the results of PISA, the literacy skills of Indonesian children are still far from the minimum average. This study aims to analyze the literacy program at the PAUD level, especially for the 5–6-year age range. The study used qualitative research with a case study approach. The subjects involved were the principal and two class teachers. Data collection was obtained from interview instruments, observation, and documentation The study used analysis method in the form of data collection, data display, data reduction, data categorization, and construction Data validation used triangulation techniques involving interviews, observations, and documentation. The results of the study showed that the literacy program with morning reading activities had fulfilled three literacy skills, including oral, alphabetic, and print awareness. While writing activities in the morning, reading the Prophet's strah has not fulfilled the three aspects of literacy skills. The novelty of this study is that literacy skills are analyzed compared to technical literacy skills, namely reading and writing. The implications of the research results are that the literate environment contributes to developing literacy skills. Research findings show that literacy skills develop in early childhood in line with the development of critical thinking skills.